Rancang Bangun Aplikasi Sistem Informasi Desa Berbasis Web di Desa Kalimati - Sopiah, Ripki Ramdani; Jannah, Hifni Fitriah Nur; Pamuji, Pandu Restu; Handayani, Nadia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study focuses on designing and developing a web-based information system for Kalimati Village using the Rapid Application Development (RAD) method. Data collection was conducted through interviews and field observations to identify system requirements. The design process employed Unified Modeling Language (UML) to model system workflows and structures, including use case and activity diagrams. The system, built with the Laravel 10 framework, features village profiles, population data, news, galleries, MSMEs, and APBDesa management. Using the RAD method enabled rapid development with iterative feedback from stakeholders, ensuring the system met village needs. This web-based platform improves data management efficiency, enhances transparency, and provides easy digital access to essential information for residents. The implementation of this system supports modern, effective, and transparent village governance.